Transcomplementation of simian immunodeficiency virus Rev with human T-cell leukemia virus type I Rex. - Krohn, K J (1993)
A molecular clone of the simian immunodeficiency virus SIVSMM isolate PBj14, lacking the ATG initiation codon for Rev protein (PBj-1.5), did not produce virus or large unspliced or singly spliced viral RNA upon transfection of HeLa cells. Low but significant levels of virus and large viral RNA production were observed upon transfection of PBj-1.5 into HeLa Rev cells expressing the rev gene of human immunodeficiency virus type 1. Furthermore, abundant virus and large viral RNA production occurred upon transfection of PBj-1.5 into HeLa Rex cells expressing the rex gene of human T-cell leukemia virus type I. Virus produced from HeLa Rex and HeLa Rev transfections was infectious, produced large amounts of virus, and was cytopathic for Rex-producing MT-4 cells. In contrast, no or only low levels of virus production were observed upon infection of H9 cells. These studies show that a defective SIV rev gene can be transcomplemented with human immunodeficiency virus type 1 Rev and with high efficiency by human T-cell leukemia virus type I Rex, and they suggest that rev-defective viruses could serve as a source for production of a live attenuated SIV vaccine.